Analysis of the Relationship between ALBI Score and APRI Score on Severity, Length of Treatment and Mortality in COVID-19 Patients at Dr. Saiful Anwar Hospital, Malang - Bogi Wibowo; Aditya Mahendra; Ahmad Ibad; Dimas Santoso; Helsa Eldatarina (Clinical and Research Journal in Internal Medicine)
Background: Covid-19 is an infectious disease caused by the SARS-CoV-2 virus and has resulted in more than 3.8 million deaths worldwide. Covid-19 can cause multiorgan complications, including hepatobiliary organs. Many assessments have been used to determine the severity and prognosis of hepatobiliary disorders, such as the Albumin Bilirubin (ALBI) score and the AST-platelet ratio index (APRI) score.